2013 13th International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD) 2013
DOI: 10.1109/nusod.2013.6633147
|View full text |Cite
|
Sign up to set email alerts
|

III-Nitride LED efficiency droop models: A critical status review

Abstract: -GaN-and AlN-based light-emitting diodes (LEDs) suffer from a severe efficiency reduction with increasing injection current (droop). Based on different theoretical models, several physical mechanisms have been proposed to explain the efficiency droop; however, conclusive experimental evidence is still missing for these proposals, and none of them is generally accepted. This presentation reviews and evaluates the main efficiency droop models currently under consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…While a semi-classical description like drift-diffusion can give a good representation of device characteristics in terms of fitting e.g. current-voltage or efficency curves [19,50], a microscopic model relying on less empirical fitting parameters would certainly provide more insight into the details of the physical processes.…”
Section: Coupling Of Transport Modelsmentioning
confidence: 99%
“…While a semi-classical description like drift-diffusion can give a good representation of device characteristics in terms of fitting e.g. current-voltage or efficency curves [19,50], a microscopic model relying on less empirical fitting parameters would certainly provide more insight into the details of the physical processes.…”
Section: Coupling Of Transport Modelsmentioning
confidence: 99%
“…While measured efficiency versus current curves can often be easily fitted with the ABC model [7], the fitting is ambiguous and its predictive power therefore limited. In fact, it has been shown that the same droop behaviour can be fitted by several different parameter sets [8]. It has also been pointed out that reduction to 1D models and structural uncertainties may considerably hamper model parameter extraction [9].…”
mentioning
confidence: 99%
“…10 The GaN-LED efficiency droop phenomenon currently receives tremendous attention but the physical mechanisms behind it are still disputed. 11 The two commonly cited explanations for the droop are Auger recombination within the MQW active region 12 and/or electron leakage from the MQW into the p-doped layers of the LED. 13 Both droop mechanisms are included in our LED model.…”
mentioning
confidence: 99%